2014
DOI: 10.1002/jcb.24731
|View full text |Cite
|
Sign up to set email alerts
|

Transitory FGF Treatment Results in the Long‐Lasting Suppression of the Proliferative Response to Repeated FGF Stimulation

Abstract: FGF applied as a single growth factor to quiescent mouse fibroblasts induces a round of DNA replication, however continuous stimulation results in arrest in the G1 phase of the next cell cycle. We hypothesized that FGF stimulation induces the establishment of cell memory, which prevents the proliferative response to repeated or continuous FGF application. When a 2-5 day quiescence period was introduced between primary and repeated FGF treatments, fibroblasts failed to efficiently replicate in response to secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…FGF memory could be dependent on HDAC‐mediated histone deacetylation or on HDAC‐dependent activation of NFκB signaling or on both. As we have reported (Poole et al, ), FGF does not change the expression of major HDACs. Thus, the search for a specific HDAC involved in FGF1 memory followed by the identification of its mechanism of action requires a comprehensive siRNA knockdown screen study involving the assessment of FGF memory establishment, NFκB signaling activity and IL1α expression.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…FGF memory could be dependent on HDAC‐mediated histone deacetylation or on HDAC‐dependent activation of NFκB signaling or on both. As we have reported (Poole et al, ), FGF does not change the expression of major HDACs. Thus, the search for a specific HDAC involved in FGF1 memory followed by the identification of its mechanism of action requires a comprehensive siRNA knockdown screen study involving the assessment of FGF memory establishment, NFκB signaling activity and IL1α expression.…”
Section: Discussionsupporting
confidence: 83%
“…We have earlier reported that transient FGF stimulation results in a sustained activation of NFκB signaling, which is critical for FGF memory establishment (Poole et al, ). IL1α (Niu et al, ; Melisi et al, ) and FGF (Muddasani et al, ; Salazar et al, ) have been demonstrated to activate the proinflammatory NFκB pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly however, the precedence of the transient induction of heritable changes after removing a stimulus has already been linked to the epithelial-to-mesenchymal transition process, creating self-renewing breast cancer stem cells from a nonstem cell population [60,61]. In another study, a "memory" of transitory FGF had a long-lasting effect on the fibroblast response to the secondary FGF stimulation; this memory reduced rather than increased their proliferation [62]. These findings underscore epigenetics and chromatin structure in controlling long-term responses, including the generation of CSCs and their phenotypic plasticity [63].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that repeated FGF1 stimulation also suppresses the proliferative response of endothelial cells and fibroblasts, a phenomenon we have coined as “FGF1 memory” (Poole et al. , ). Together, these data strongly suggest that continuous or prolonged FGF1 exposure suppresses preadipocyte self‐renewal and/or the adipogenesis process itself.…”
Section: Discussionmentioning
confidence: 99%